2001
DOI: 10.1108/13639510110390936
|View full text |Cite
|
Sign up to set email alerts
|

A social constructionist account of police culture and its influence on the representation and progression of female officers

Abstract: The police organisation receives much media attention regarding its record on Equal Opportunities. Research suggests that the organisational culture in police organisations plays a major role in impeding the progress of women. Using repertory grid technique, the culture of a police force, conceptualised at the level of performance value judgements or recipe knowledge was investigated. It is argued that rank, rather than gender has the greatest influence on the content of performance value judgements and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 26 publications
2
70
0
Order By: Relevance
“…Similar strong macho culture and gendered structures and processes have been identified in other research on the police service Davies and Thomas, 2008;Dick and Jankowicz, 2001;Doran and Chan, 2003;Leishman, Loveday and Savage, 2000;Martin 1999;Waddington, 1999).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Similar strong macho culture and gendered structures and processes have been identified in other research on the police service Davies and Thomas, 2008;Dick and Jankowicz, 2001;Doran and Chan, 2003;Leishman, Loveday and Savage, 2000;Martin 1999;Waddington, 1999).…”
Section: Discussionmentioning
confidence: 60%
“…Ridgeway and Correll (2004) argue that when women enter a particular field and that field is seen to become feminised, it subsequently becomes devalued. Therefore, those who choose to pursue 'appropriate feminine roles' might well be limiting their career prospects because feminine roles are associated with lower performance values or 'recipe knowledge' (Dick and Jankowicz, 2001). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a more recent British study, Loftus (2009) has suggested that there is more commonality than difference between these cultures. Of course, on closer examination there appear different police sub-cultures (Dick and Jankowicz, 2001;Herbert, 1998) -'firearms officers' will probably have a rather different understanding of what counts as 'real policing' to 'traffic cops' as they, in turn, will have to those involved in policing domestic violence. Moreover, Chan (1996) is surely right to suggest that cultures do not determine the actions of individuals.…”
Section: Durkheim's the Elementary Forms Of The Religious Lifementioning
confidence: 99%